2020
DOI: 10.1111/tmi.13400
|View full text |Cite
|
Sign up to set email alerts
|

Substantial reduction in child stunting is differentially associated to geographical and socioeconomic disparities in Misiones Province, Argentina

Abstract: Objective: To estimate trends in the prevalence of child stunting in the population of children under 5 years of age covered by public health programs, between 2009 and 2014 in Misiones, Argentina. Methods: Using Bayesian model-based geostatistics, we evaluated 724,872 anthropometric measurements corresponding to 110,633 children. In order to identify disparities at local scale we evaluated the hypotheses of a differential reduction of stunting according to the geographical location (at two-level spatial resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, we consider that they could have contributed to the reduction of food insecurity and possibly child undernutrition, especially in the province of Misiones, which recorded the largest decrease from C1 to C2. In line with this hypothesis, Nuñez et al (2020) informed a substantial relative decrease (41.8%) in the prevalence of stunting among children under 5 years of age covered by public health programs in the province of Misiones.…”
Section: Discussionmentioning
confidence: 83%
“…However, we consider that they could have contributed to the reduction of food insecurity and possibly child undernutrition, especially in the province of Misiones, which recorded the largest decrease from C1 to C2. In line with this hypothesis, Nuñez et al (2020) informed a substantial relative decrease (41.8%) in the prevalence of stunting among children under 5 years of age covered by public health programs in the province of Misiones.…”
Section: Discussionmentioning
confidence: 83%
“…A study in India analyzed data across 640 districts in India and found that the prevalence of stunting was higher among poorer populations in northern India compared to eastern and southern parts of India [7]. Additionally, a study in Argentina found regional disparities with higher prevalence values in the north and northeast regions [8]. A better understanding of these disparities provides a precision public health tool to target public policies to those populations with the greatest need in order to reduce health disparities [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study in Argentina found regional disparities with higher prevalence values in the north and northeast regions [8]. A better understanding of these disparities provides a precision public health tool to target public policies to those populations with the greatest need in order to reduce health disparities [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations